Validation and reliability of beach volleyball skill test instruments - Zetou, E.; Giatsis, G.; Tzetzis, G. (Journal of Human Movement Studies, 2005)
The purpose of this study was to develop three beach Volleyball (BV) skill tests and then check their reliability and validity. BV as a new sport requires skill tests to evaluate the athletes' performance. Therefore, after a pretest to athletes, a training Intervention program could be followed and useful results for the coaches could be obtained. For this reason, and after taking into account all the parameters and special characteristics of the game, specific tests were constructed by expert beach volleyball coaches for the evaluation of the set, the pass and the serve skill. The sample consisted of forty (N = 40) BV players (21 male and 19 female), within an age band of 13-26 years (M =17.22, SD = 6.08). According to Safrit (1986) a test should first measure what it was intended to measure. Secondly, it should be reliable with reliability being defined as the degree of consistency of the test. Four types of validity were examined: logical, content, criterion and construct validity, and two types of reliability: internal consistency (intraclass) and stability of the tests were also examined in this study. The results indicated that the BV skill tests were valid and reliable instruments and could therefore be used by coaches to test the ability of players to set, pass and serve the ball effectively.